2009
DOI: 10.1259/bjr/93776392
|View full text |Cite
|
Sign up to set email alerts
|

Glue ablation of a late-presentation urinary fistula after partial nephrectomy

Abstract: ABSTRACT. Urinary fistula is an acknowledged complication of partial nephrectomy. We describe a case of a urinary fistula that failed to respond to conventional treatment and the subsequent use of percutaneous HystoacrylH glue to achieve its resolution. Case reportA 57-year-old woman underwent an uncomplicated right lower pole partial nephrectomy for Fuhrman grade 3 pT1NxMx clear cell renal cell carcinoma, through a right loin 11th rib incision. At outpatient review meeting 1 month after discharge, she was we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…There has also been a case reported in which a cyanoacrylate glue was percutaneously injected and used to close a persistent urine leak in a patient who was medically unfit for surgery. 89 This technique is interesting and bears further investigation.…”
Section: Presentation and Diagnosismentioning
confidence: 96%
“…There has also been a case reported in which a cyanoacrylate glue was percutaneously injected and used to close a persistent urine leak in a patient who was medically unfit for surgery. 89 This technique is interesting and bears further investigation.…”
Section: Presentation and Diagnosismentioning
confidence: 96%
“…In addition to local hemostasis, it is used to seal wounds and fistulas, and for nephroplasty, fixation of ureteral anastomosis, urethral skin, and bladder colon fistulas. 3,4 It has also been reported that transurethral injection of fibrin glue improved urinary leakage after partial nephrectomy. 5 The injected fibrin glue remains in a solid-state for approximately 24 h and then denatures into a gel state in approximately 5 days.…”
Section: Discussionmentioning
confidence: 95%
“…More recently the application of cyanoacrylate glues has been reported in different branches of surgery for endoscopic treatment of refractory bile leaks, gastroenteric fistulae, intracranial vascular malformations and also for the management of urinary fistulas. To our knowledge few cases in literature described the endoscopic utilization of cyanoacrylate in repairing UF after urological maneuvers and until now there are only 4 single cases reports of percutaneous successful utilization of cyanoacrylate glue in repairing UF after PN have been reported till date (5,6). In addition, two clinical case series: one of 13 cases in 9 years by Muto et al that reported the use of cyanoacrylate glue in repairing endoscopic percutaneous and endovaginal urinary fistula of various etiologies with a high success rate and few complications (7).…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%